Best to Laugh : A Novel - Landvik, Lorna, 1954- (Book collections on Project MUSE., 2014)
No one steps up to life's banquet, holds out her tray and orders, "Grief, please!" But as a child, Candy Pekkala was served a heaping helping of it. Every buffet line has a dessert section, however, and when a cousin calls with a Hollywood apartment to sublet, it seems as though Candy is finally offered something sweet. It's good-bye to Minnesota and hello to California, where a girl who has always lived by her wits has a real chance of making a living with them. With that, the irrepressible Lorna Landvik launches her latest irresistible character onto the world stage -- or at least onto the dimly lit small stage where stand-up comedy gets its start. Herself a comic performer, Landvik taps her own adventurous past and Minnesota roots to conjure Candy's life in this strange new Technicolor home. Her fellow tenants at Peyton Hall include a female bodybuilder, a ruined nightclub impresario and a well-connected old Romanian fortune-teller. There are game show appearances and temp jobs at a record company and an establishment suspiciously like the Playboy Mansion, and of course the alluring but not always welcoming stage of stand-up comedy. As she hones her act, Candy is tested by humiliation, hecklers and the inherent sexism that insists "chicks aren't funny." Written with the light touch and quiet wisdom that have made her works so popular, this is classic Lorna Landvik -- sometimes so funny you'll cry, sometimes so sad you might as well laugh and always impossible to put down